Color‐Selective and CMOS‐Compatible Photodetection Based on Aluminum Plasmonics. (5th August 2014) - Zheng, Bob Y.; Wang, Yumin; Nordlander, Peter; Halas, Naomi J.
<x xml:space="preserve">Abstract</x> A color‐selective, band‐engineered photodetector is demonstrated. The device uses two Schottky junctions to accumulate charge in an energy well, which results in photocurrent gain and a plasmonic aluminum grating for photocurrent enhancement and red–green–blue color selectivity. This work provides a more intelligent way to design imaging sensors by integrating amplifiers and color filters directly into pixels. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>